Passive SAR satellite (PASSAT) system: airborne demonstrator and first results. Issue 2 (28th January 2019) - Atkinson, George; Sayin, Alp; Stove, Andrew; Underwood, Craig I.; Cherniakov, Mikhail; Antoniou, Michael
Abstract : This study presents the development and execution of an airborne experimental campaign as a part of the continuing investigation of a passive synthetic aperture radar using digital television broadcasting stations as illuminators of opportunity, and micro‐/nano‐satellite receivers in low earth orbit. For the flight experiments, a hardware demonstrator was developed that utilised two receiving antennas, allowing both cross‐correlation and auto‐correlation range compression schemes, and was mounted to an airborne platform to image stationary rural areas up to 50 km from the transmitter. This study presents the first image results of these experiments as well as initial analysis of image formation aspects, including range compression scheme and effects on the image quality of the signal to noise on the reference channel.